The Effects of Employees’ Assistance Programme on Good Governance in Nigeria - Aramide Arinola, Kuforiji; Gabriel Izokpu, Oikhala (Journal of Governance and Public Affairs, 2025)
Employers and employees have goals for their working relationship; most times monetary reward is insufficient to earn employee’s affective commitment.  This study therefore examines the utilisation, effectiveness, and impact of Employee Assistance Programs (EAPs) on compensation, employee wellness and job satisfaction within selected organisations using Lagos State, Nigeria as case study. Using a cross-sectional survey design, data from 150 employees across various sectors were analysed. Findings revealed that there is limited awareness and utilisation of EAPs with significant variations across sectors. The study identified that EAPs are vital for mental wellness and job satisfaction in a work place, suggesting they should be integrated as indirect compensation for workers because they are preconditions for realisation of the organisational goals and good governance of the country. The research concludes that EAPs foster employees’ commitment and enhance organisational performance, recommending increased awareness and effective communication of EAP benefits